(untitled) (Світ фінансів, 2017)
Врода Л. В. Шляхи вдосконалення механізму формування статутного капіталу банківcьких установ. Розкрито значення статутного капіталу банківської установи у механізмі формування власного капіталу. Проаналізовано динаміку обсягів капіталу і статутного капіталу банків України. Вказано проблеми та шляхи вдосконалення механізму формування статутного капіталу комерційних банків. Varoda L. Ways of improvement of the mechanism of formation of the bank authorized capital. The importance of the authorized capital of a bank the mechanism of formation of its own capital is covered. The dynamics (changes) of amount of the capital and authorized capital of banks in Ukraine are analysed. Factors of protection of the own capital in some banks of Ukraine. The problems and the ways of improvement of the mechanism of formation of the authorized capital in commercial banks are specified.